Flow state and autonomic response patterns during sensory rejection tasks using the Uchida-Kraepelin Test - Hiroyuki Kuraoka; Mitsuo Hinoue; Chikamune Wada; Shinji Miyake (PLoS ONE, 2025)
This study investigated the relationship between flow state and autonomic nervous system activity indices in 18 healthy male participants using a mental arithmetic task (Uchida-Kraepelin [U-K] test)—known as a sensory rejection task. The experiment consisted of two sets, each comprising a 5-minute rest period, followed by a 15-minute task period with varying task conditions of self-paced, to be performed at own pace, and competitive, as per the instruction “Always do as many calculations as possible, aiming to exceed the preceding performance.” In the subjective assessment, the flow, time perception, subjective mental workload, and feelings of fatigue were evaluated. Autonomic nervous system activity indices were continuously monitored. The results indicate that the U-K test, which is a low-difficulty, monotonous task, failed to induce a flow state. Physiological responses to mental tasks showed an increased heart rate, suggesting a Pattern 1 response. The participants who entered a flow state, based on their flow and time perception scores, had a decreased heart rate immediately after the task, supporting the association between the flow state and Pattern 2 responses. Considering the relationship between flow and Pattern 2 responses, it is recommended to assess flow using multiple physiological markers, including blood pressure.